Drowned Out: Silence in Junot Díaz’s Short Stories - Ambio, Marissa L. (Revista Canadiense de Estudios Hispánicos, 2021)
This study proposes the silence that defined Junot Díaz, as revealed in his New Yorker (2018) essay “The Silence,” also permeates his fiction. I explore how the artistic and ideopolitical function of silence in Drown (1996) informs violence and masculinity. The representations of sound and its absence, though seemingly innocuous, articulate hierarchies that reinforce and contest masculine codes, while gestures transform them. Drown’s stories are “moment of truth” narratives predicated on the rupture of silence and subsequent protagonist development. This essay elucidates Yunior’s complex relation to silence and his evolution from vocal boy to reticent adolescent and, eventually, to the author-narrator of the collection’s stories.